Horizontal transfer of antibiotic resistance between trans-gram bacteria in surface water of Dhaka city - Mostafa, Fariha Binte (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.